2019
DOI: 10.1152/ajpheart.00510.2018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated bone marrow sympathetic drive precedes systemic inflammation in angiotensin II hypertension

Abstract: Increased sympathetic nervous system activity is a hallmark of hypertension (HTN), and it is implicated in altered immune system responses in its pathophysiology. However, the precise mechanisms of neural-immune interaction in HTN remain elusive. We have previously shown an association between elevated sympathetic drive to the bone marrow (BM) and activated BM immune cells in rodent models of HTN. Moreover, microglial-dependent neuroinflammation is also seen in rodent models of HTN. However, the cause-effect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Three weeks after viral injections in nodose ganglia, we performed direct electrophysiological recordings of afferent vagal activity rostral to both LNG and RNG simultaneously using a modified decorticated artificially perfused rat (DAPR) in situ preparation 2 weeks following viral injections in nodose ganglia. The modification to the previously described DAPR [33][34][35] included retention of an intact GI tract with a separate perfusion system allowing specific targeting of GI vagal afferents by delivering ghrelin or CCK via arterial GI circulation (see schematics of the modified in situ DAPR in Figure 2A). Wistar rats (male, 6 weeks old, 100-120 g, n = 8) were briefly anesthetized with isoflurane (4%), exsanguinated, decorticated (decerebrated at the precollicular level as originally described in [36]), and immediately submerged into ice-chilled artificial cerebrospinal fluid (aCSF; composition in mM: 125 NaCl, 24 NaHCO3, 3KCl, 2.5 CaCl2, 1.25 MgSO4 and 1.25 KH2PO4, 10 dextrose, pH 7.3) (Sigma-Aldrich and Fisher, USA).…”
Section: Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Three weeks after viral injections in nodose ganglia, we performed direct electrophysiological recordings of afferent vagal activity rostral to both LNG and RNG simultaneously using a modified decorticated artificially perfused rat (DAPR) in situ preparation 2 weeks following viral injections in nodose ganglia. The modification to the previously described DAPR [33][34][35] included retention of an intact GI tract with a separate perfusion system allowing specific targeting of GI vagal afferents by delivering ghrelin or CCK via arterial GI circulation (see schematics of the modified in situ DAPR in Figure 2A). Wistar rats (male, 6 weeks old, 100-120 g, n = 8) were briefly anesthetized with isoflurane (4%), exsanguinated, decorticated (decerebrated at the precollicular level as originally described in [36]), and immediately submerged into ice-chilled artificial cerebrospinal fluid (aCSF; composition in mM: 125 NaCl, 24 NaHCO3, 3KCl, 2.5 CaCl2, 1.25 MgSO4 and 1.25 KH2PO4, 10 dextrose, pH 7.3) (Sigma-Aldrich and Fisher, USA).…”
Section: Reportmentioning
confidence: 99%
“…Simultaneous recordings of the left and right afferent nerve activity (LNG and RNG; Figure 2A) were obtained using glass suction electrodes (tip diameter, 0.2-0.3 mm), amplified (20-50K) and filtered (3-30K), sampled at 5 kHz (CED, Cambridge) and monitored using Spike2 (CED). The perfusate flows (19-24 mL/min for brainstem and 1.5-3.5 mL/min for GI perfusion) were adjusted to mimic physiologic perfusion levels and maintain the health of the preparation [33][34][35]37]. Vasopressin (1.25-4 nM final concentration, Sigma-Aldrich, USA) was added to the brainstem perfusate to increase vascular resistance and aid in maintenance of adequate brainstem perfusion to preserve autonomic reflexes [33][34][35].…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Human T lymphocytes can also reportedly produce components of the renin–angiotensin system, and this activity is enhanced, in a feedforward manner, with exposure to Ang II (Coppo et al., 2008). Recent research found that serum complement 3, a central hub of the complement IS, is elevated in prehypertensive patients (Bao et al., 2017), and elevated IS markers have also been demonstrated before development of HTN in rodent models (Ahmari et al., 2019; Santisteban et al., 2017), suggesting possible causation. Indeed, infusion of activated lymphocytes in patients with metastatic melanoma has been found to increase BP (Balsari et al., 1986).…”
Section: Immune System Dysregulation Is a Hallmark Of Systemic Hypertmentioning
confidence: 99%
“…Three weeks after viral injections in nodose ganglia, we performed direct electrophysiological recordings of afferent vagal activity rostral to both LNG and RNG simultaneously using a modified decorticated artificially perfused rat (DAPR) in situ preparation 2 weeks following viral injections in nodose ganglia. The modification to the previously described DAPR [58][59][60] included retention of an intact GI tract with a separate perfusion system allowing specific targeting of GI vagal afferents by delivering ghrelin or CCK via arterial GI circulation (see schematics of the modified in situ DAPR in Fig. 2A).…”
Section: Modified Decorticated Artificially Perfused Rat (Dapr) Prepamentioning
confidence: 99%